Whither Asperger’s post DSM-5? An opinion piece - Volkmar, F.R.; Woodbury-Smith, M. (Review Journal of Autism and Developmental Disorders, 2024)
Although first described in 1944 (the year the description of infantile autism), Asperger’s syndrome attracted little attention until the publication by Lorna Wing in early 1980. Over time, different views of the definition of Asperger’s syndrome developed. By the time of the Third Edition of the American Psychiatric Association’s Diagnostic and Statistical Manual and the Tenth Edition of the World Health Organization’s International Classification of Disease, enough information had accumulated to include the condition within the broader autism category. Asperger’s syndrome remained a focus of research interest and debate until its exclusion in the DSM-5 in 2013. We argue that the decision to remove Asperger’s syndrome 10 years ago as a distinct condition was premature. A discussion of the tensions around defining Asperger’s and concerns now arising due to the lack of this diagnostic category for new cases is provided. © 2024, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Asperger’s disorder; Autism spectrum disorder; Autistic disorder; Classification; DSM-5; dept.sed; peer-reviewed